Effect of liquidity risk in the profitability of banks: comparison between Dhaka Bank Ltd and the overall industry - Shams, Zuhaier (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.